2019
DOI: 10.1016/j.esxm.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Phenotypic Transformation of Corpus Cavernosum Smooth Muscle Cells After Cavernous Nerve Crush Injury by Down-Regulating P38 Mitogen-Activated Protein Kinase Expression

Abstract: Introduction: Cavernosal nerve (CN) injury is commonly caused by radical prostatectomy surgery, and it might directly lead to erectile dysfunction (ED). Currently, the role of mitogen-activated protein kinase (MAPK) family proteins in phenotypic transformation of corpus cavernosum smooth muscle cell (CCSMC) after CNs injury is poorly understood. Aim: To investigate the role of p38 MAPK in hypoxia-induced phenotypic transformation of CCSMCs after CN injury. Methods: In total, 20 SpragueeDawley rats (male and 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Unlike the findings of Chen et al. in a study of neurologically injured rats, 36 in the present experiment, we found by RT–qPCR and Western blot that in the BCNI group of rats, at both 14 and 28 days, the phosphorylation level of p38 MAPK was elevated, and this change was partially reversed after LIPUS treatment. Therefore, we can reasonably speculate that p38 MAPK is a potential upstream regulatory signal of YAP/TAZ that regulates the general mechanism of penile tissue repair after injury.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike the findings of Chen et al. in a study of neurologically injured rats, 36 in the present experiment, we found by RT–qPCR and Western blot that in the BCNI group of rats, at both 14 and 28 days, the phosphorylation level of p38 MAPK was elevated, and this change was partially reversed after LIPUS treatment. Therefore, we can reasonably speculate that p38 MAPK is a potential upstream regulatory signal of YAP/TAZ that regulates the general mechanism of penile tissue repair after injury.…”
Section: Discussioncontrasting
confidence: 99%
“…Several histological studies have been performed for CC and sinusoids by utilizing thin sections with H&E staining 41,42 . Histological analyses with such thin sections of H&E staining generally revealed only part of the CC structures thus not revealing the entire 3D structures 43‐45 . The currently identified sinusoid structures showed variations in their sizes revealed by reconstructed 3D histological images.…”
Section: Discussionmentioning
confidence: 99%
“…The cells used in the experiments were all within 4 passages. The method of primary cell culture has already been described (Chen et al, 2019).…”
Section: Methodsmentioning
confidence: 99%